Financial technology: a review of extant literature. Issue 1 (1st November 2019) - Sangwan, Vikas; , Harshita; Prakash, Puneet; Singh, Shveta
Abstract : Purpose: This paper aims to undertake a thematic review of academic papers on financial technology (FinTech) to identify three broad categories for the purpose of classifying extant literature. The paper summarizes the research and findings in this emerging field. Thereafter, it identifies the gaps and provides directions for further research. Simultaneously, the paper collates technical terms related to FinTech that appear repeatedly in each category and explains them. Finally, the study highlights the lessons that growing FinTech firms and their regulators can learn from the experiences of their counterparts across the globe. Design/methodology/approach: A systematic review of literature consisting of 130 studies (social science research network [SSRN]-29 papers, Scopus-81, other sources-20) on FinTech is carried out in this thematic paper. Findings: This thematic paper divides FinTech into three themes, i.e. financial industry, innovation/technology and law/regulation. The paper suggests that a thorough impact of FinTech on various stakeholders can be understood using three dimensions, namely, consumers, market players and regulatory front. It is noted that FinTech is in its nascent phase and is undergoing continuous development and implementation through product and process innovation, disruption and transformation. Research limitations/implications: The paper reports that FinTech promises huge potential for further study by various stakeholders in the FinTech industry – from academia to practitioners to regulators. Practical implications: The paper summarizes lessons that could be of significance for FinTech users, producers, entrepreneurs, investors, policy designers and regulators. Originality/value: The paper is believed to add value to the understanding of FinTech in light of the emerging threats and opportunities for its various stakeholders.